The constitutional protection of minorities and the influence of elements of social differentiation on state organization. A survey on some remarkable examples from Asia and Latin America - Viola, Pasquale (2020)
The influence of minorities on state organizations and their protection are common features in constitutional orders, especially in those that emphasize the importance of the ethnic factor. Over the past decades, the revival of cultural and ethnic factors has led to the acknowledgment of the existence of culture-specific rules as elements of social identification. In Asia and Latin-America, one can spot the evolution of contemporary legal and social frameworks according to the concept of minority, leading to the recognition of the importance –and the existence– of cultural diversity